Atlas of forgotten places journey to abandoned destinations from around the globe - Elborough, Travis (White Lion Publishing, 2021)
Introduction -- Vacant properties -- Unsettled situations -- Dilapidated destinations -- Journeys ended -- Obsolete institutions.
Includes bibliographical references (pages 202-203) and index
Keywords: Historische Stätte; Historische Geografie; Geheimnisvolle Stätte; Ortswüstung; Elborough, Travis / Travel; Historic sites / Description and travel; Historic industrial sites / Description and travel; Curiosities and wonders / Miscellanea; Voyages and travels; History / Miscellanea; Abandoned buildings; Lost architecture; journeys; abandoned buildings; Curiosities and wonders; History; Travel; world atlases; Trivia and miscellanea; World atlases; Atlas mondiaux; Miscellanées; Atlas